(untitled) (IAHS Medical Journal, 2022)
Background: In recent years, large-scale natural disasters have frequently occurred in various parts of the world including Bangladesh due to its geographical location and the associated losses have increased. In order to avoid risks and damage, to strengthen resilience to natural disasters, national and local governments and local community need to be prepared. The purpose of the study is to identify consciousness and preparation for frequently occuring natural calamities by the island dwellers in Sandwip. Materials and methods: This was a descriptive type of cross-sectional study performed in the island of Sandwip of Chattogram for a period of 12 (Twelve) months. Sample size was 300 and sampling technique was convenient type of non-probability sampling. Data were collected by face to face interview with pretested questionnaire containing both structured and unstructured questions. Results: The mean ages of the respondents were 49.57 years. 51.3% were illiterate, most of them i.e., 49.2% were from lower class. Regarding occupation, 42.8% were housewife, 24.4% farmer and 7.7% fisher man. Maximum i.e 46.7% respondents were informed about natural calamities from television, majority 70% had not got trained, and only 30% got training from different institution. To remain safe from natural calamities, maximum carefully select the site for residence i.e 52.3% and 44.7% select a safe place to stay during an emergency. 36.7% respondents follow the official weather forecast and warning regularly for evacuation. About 92% had no insurance coverage for their household or business. According to the level of preparedness score, 54% had no preparation, 41.7% were partially prepared and 4.3% had complete preparation to tackle the natural calamities. According to the level of awareness score, only 35.3% were aware about their situation regarding preparedness. Conclusion: Whilst natural disasters cannot be prevented, working together by Public Private Partnership (PPP) utilizing the result and engaging skills to fight against any disaster, attempt can be taken to minimize the effect of disasters, which will ultimately provide the safety and security to the people of Sandwip and costal areas of Bangladesh. IAHS Medical Journal Vol 5(1), June 2022; 27-31